Study of the Effects of Training and Coaching on Increasing the Performance of Micro, Small and Medium Enterprises (MSMEs) assisted by the UMKM Center in Semarang City - Achmad - Zaenuddin; Noor - Suroija; Taviyastuti - Taviyastuti; Makmun - Riyanto; Rif'ah Dwi Astuti (Admisi dan Bisnis, 2022)
Most of the business actors in Central Java are micro, small, medium and large scale business actors (MSMEs), which account for 99.19% of the total non-agricultural businesses in Central Java. Survey data shows that during the pandemic, 94.69% of businesses experienced a decline in sales. Based on the business scale, the decline in sales of more than 75% was experienced by 49.01% ultra-micro businesses, 43.3% micro businesses, 40% small businesses, and 45.83% medium businesses. The advantage of MSMEs in surviving the storm of crises for various reasons. First, in general, MSMEs produce consumer goods and services that are close to the needs of the community. Second, MSMEs do not rely on imported raw materials and make more use of local resources in terms of human resources, capital, raw materials and equipment. Third, MSE businesses generally use relatively low capital. Facing the Covid 19 pandemic, the MSME Center is conducting training and coaching/assistance so that MSMEs can adapt well and be able to maintain their business. This study aims to analyze the effect of training and coaching on the performance of SMEs assisted by the UMKM Center in Semarang City. The method used is descriptive analysis with qualitative and quantitative approaches. Quantitative data analysis using multiple regression